Patent op leven? - Melle, Ullrich; Janssens, Frederik; Jacobs, Roger; Peeters, Jef; van de Ven, Jeanneke (Tremelo: Wervel, 1998)
"Ullrich Melle en Frederik Janssens, Roger Jacobs, Jef Peeters, Jeanneke van de Ven, Etc."